2021
DOI: 10.2147/idr.s329563
|View full text |Cite
|
Sign up to set email alerts
|

Outbreak of Multidrug-Resistant OXA-232-Producing ST15 Klebsiella pneumoniae in a Teaching Hospital in Wenzhou, China

Abstract: Background OXA-232-producing carbapenem-resistant Klebsiella pneumoniae (CRKP) has the potential to become the “third epidemic” of carbapenem-resistant Klebsiella strain after KPC-2 and NDM in China. We investigated the first outbreak of CRKP in the First Affiliated Hospital of Wenzhou Medical University. Methods We collected 610 clinical isolates of CRKP from the First Affiliated Hospital of Wenzhou Medical Universi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 31 publications
4
18
0
Order By: Relevance
“…The rates of resistance to colistin and tigecycline were 5.13% and 8.55%, respectively (see Table S2). The antibiotic resistance experiment suggested that the OXA-232-CRKP isolates presented a multidrug-resistant profile with different levels of resistance to carbapenems, as reported previously ( 23 ).…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…The rates of resistance to colistin and tigecycline were 5.13% and 8.55%, respectively (see Table S2). The antibiotic resistance experiment suggested that the OXA-232-CRKP isolates presented a multidrug-resistant profile with different levels of resistance to carbapenems, as reported previously ( 23 ).…”
Section: Resultssupporting
confidence: 82%
“…Qin et al reported that the infection incidence of patients who had CRKP colonization in the intestinal tract and nasopharyngeal tract was almost 45.9% in the ICU at Huashan Hospital (Shanghai, China), which posed a true threat to public health because antimicrobial agents are rarely used to treat multidrug- resistant pathogens ( 21 ). Although the environment has been considered a reservoir for pathogens in the ICU and nosocomial outbreaks of OXA-232-CRKP have increased in recent years, there is limited literature reporting on the relationship and transmission of OXA-232-CRKP between the environment and patients ( 9 , 22 , 23 ). In this study, we focused on the OXA-232-CRKP that was first reported by Potron et al in 2013 and then spread throughout the world in recent years ( 12 ), whereas limited literature focuses on colonization in hospitals and patient infections.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The OXA-48 enzyme has been reported in Beijing, 24 Shanghai 25 and Taiwan. 26 In recent years, OXA-232-producing (a variant of OXA-48 family, and the third most common OXA-48-like carbapenemase worldwide) Enterobacteriaceae began to appear in China, while OXA-232-producing Klebsiella pneumoniae is the most common in Shanghai, 27 Zhejiang 28 and other regions. According to the above reports, the OXA-48-like enzyme has begun to spread in China.…”
Section: Introductionmentioning
confidence: 99%
“…OXA-232-producing K. pneumoniae strains have been reported in Zhejiang and Shanghai, China (Shen et al, 2020b;Shi et al, 2020;Jia et al, 2021), but to our knowledge, no comprehensive phylogenetic analysis for ST15 K. pneumoniae isolates collected from various countries has been performed before. Moreover, a study by Zhu et al in Yancheng, China reported clonal dissemination of ST15 OXA-232-producing K. pneumoniae strains (Zhu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%